Microbial Contaminants Evaluation of White Pomegranate Peel, Seeds, and Beetroot as Validation of Herbal Raw Material Quality - Faisal, Faisal; Ramadhan, Majida; Rofiidah, Anisatul; Nirwana, Linggar (Universitas Brawijaya, 2025)
Pomegranate (Punica granatum L.) and beetroot (Beta vulgaris) are recognized for their numerous health benefits, attributed to their bioactive. However, the use of natural ingredients as traditional medicine requires attention to microbiological safety, given the potential for contamination by pathogenic microbes. This study aims to analyze microbial contamination on the skin and seeds of white pomegranate (Punica granatum L.) and beetroot (Beta vulgaris). Samples were tested at the Microbiology Laboratory of the Islamic University of Malang using the Total Plate Count (TPC) method to count total microorganisms and qualitative tests to detect the presence of pathogenic microorganisms, such as Salmonella sp. and Staphylococcus aureus. The results showed that the total microbes and mold/yeast for all samples were within the safe limits set by the Food and Drug Administration (BPOM). The highest TPC was found in white pomegranate peel extract (2,1x10? CFU/g), while the highest Total Yeast and Mold Count (TYMC) was found in white pomegranate seed extract (8,2x10? CFU/g). Although Salmonella sp. was not detected in all samples, Staphylococcus aureus was identified positively in white pomegranate seed extract. These findings underscore that, although the total microbial count is low, contamination by specific pathogens can occur, most likely during post-harvest handling. The presence of Staphylococcus aureus highlights the importance of implementing strict sanitation controls and Good Manufacturing Practices (GMP) in the processing of herbal raw materials to ensure product safety.